Investigation on Mixing Performance and Droplet Generation of Dissimilar Liquids through T-junction and Offset T-junction Microchannels - Hawa, Ringkai (Universiti Malaysia Sarawak, 2022)
To date, microfluidic device has contributed significantly in biotechnology and life sciences due to their fast response time, low consumption of samples and high sensitivity. Although it is widely utilized in bio-, nano-, and environmental technologies, there are still limited experimental investigations on the micromixing process of dissimilar liquids i.e., in cosmetics, construction and biofuel production. In this study, the mixing index of propan-2-ol and water, water and sodium chloride solution, propan-2-ol and sodium chloride solution were characterized and reported at 5 ≤ Re ≤ 50 inside the 750 μm-radius of fabricated T-junction and offset T-junction microfluidic channel. By using RGB colour model method, both microchannels for miscible mixing experiments show better mixing index at high Reynolds number (Re) of 40 and 50 due to the significant convection which is caused by the effect of stretching and thinning of liquid lamellae. Meanwhile, for immiscible mixture, offset T-junction yielded superior mixing performance than T-junction microchannel at both low and high Re. Hence, due to the fact that offset T-junction performs better than T-junction, the study was furthered by investigating the behaviours of water-in-oil droplet at interfacial surface within offset T-junction microchannel having different size i.e., radius of 400 μm, 500 μm, 750 μm and 1000 μm using micro-PIV software. The results showed that experimental velocity of the water droplet holds good agreement with theoretical values, having minimal difference as low as 0.004 mm/s for the case of microchannel with radius 750 μm. A maintained average velocity of 0.055 mm/s for channel with radius of 1000 μm was achieved, meanwhile the other channels showed a good average velocity data i.e., an increase from 0.15 mm/s to 0.20 mm/s for channel radius of 500 μm. In addition, a major elevation for mean velocity from 0.055 mm/s to 0.15 mm/s for channel with radius of 750 μm was also seen. The proposed design of microfluidic device especially offset T-junction offers more efficient and better results in micromixing study of immiscible liquids.